2002
DOI: 10.1046/j.1468-1331.2002.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill training with partial body weight support and physiotherapy in stroke patients: a preliminary comparison

Abstract: Background and Purpose-The purpose of this study was to compare treadmill and electromechanical gait trainer therapy in subacute, nonambulatory stroke survivors. The gait trainer was designed to provide nonambulatory subjects the repetitive practice of a gait-like movement without overexerting therapists. Methods-This was a randomized, controlled study with a crossover design following an A-B-A versus a B-A-B pattern.A consisted of 2 weeks of gait trainer therapy, and B consisted of 2 weeks of treadmill therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 24 publications
0
46
1
1
Order By: Relevance
“…44,45 Conventional physiotherapy-with or without treadmill activities and of modest intensity-have also led to improved walking skills, including level of independence and walking speed, when started 6-18 months after stroke. [46][47][48][49][50][51][52][53] Although patients who make large gains tend to be among those with more modest impairments, these studies confirm the potential to improve function by trying a pulse of goal-directed physical therapy at any time after stroke.One approach for massed practice is treadmill training with partial support of body weight. This strategy is developed from studies of cats with transected spinal cords, 54 but this theoretical basis seems less translatable to humans than most reports suggest.…”
mentioning
confidence: 91%
“…44,45 Conventional physiotherapy-with or without treadmill activities and of modest intensity-have also led to improved walking skills, including level of independence and walking speed, when started 6-18 months after stroke. [46][47][48][49][50][51][52][53] Although patients who make large gains tend to be among those with more modest impairments, these studies confirm the potential to improve function by trying a pulse of goal-directed physical therapy at any time after stroke.One approach for massed practice is treadmill training with partial support of body weight. This strategy is developed from studies of cats with transected spinal cords, 54 but this theoretical basis seems less translatable to humans than most reports suggest.…”
mentioning
confidence: 91%
“…3 Losing one's mobility is the greatest loss for stroke patients. 4 Recovering the ability to walk is an important rehabilitation goal 5 and is one of the greatest concerns for the patient, family, and therapist. 6 However, most stroke patients have a slower gait cycle because of the difficulty in moving their affected extremity 7 and thus, find it challenging to maintain balance when walking due to their asymmetric step and shorter stride.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that these techniques are based on the principles of plasticity in the adult human brain which allow for reorganization of nervous networks, and this plasticity can be activated by repeated task-specific training. These restorative programs are focused on the functional improvement of the upper extremity 307,308 or on the recovery of gait 309,310 , offering a promising tool for the treatment of stroke patients with residual disability.…”
Section: Rehabilitation Programsmentioning
confidence: 99%
“…In patients with <50% stenosis in NASCET, there was no significant reduction in the ipsilateral stroke risk among those treated with endarterectomy compared with those treated medically 508 . A meta-analysis of pooled data from the ECST, NAS-CET and Veterans Affairs Trial 309 showed that carotid surgery increased the 5-year risk of ipsilateral ischemic stroke in patients with less than 30% stenosis (n=1746, absolute risk reduction -2.2%, p=0.05), had no effect in patients with 30%-49% stenosis (1429, 3.2%, p=0.6), was of marginal benefit in those with 50%-69% stenosis (1549, 4.6%, p=0.04), and was highly beneficial in those with 70% stenosis or greater without near-occlusion (1095, 16.0%, p<0.001). There was a trend towards benefit from surgery in patients with near-occlusion at 2-year follow-up (5.6%, p=0.19) 262 , but no benefit at 5 years (-1.7%, p=0.9) 509 .…”
Section: Carotid Artery Endarterectomymentioning
confidence: 99%